(3GdGSJKeGQ aj HfjI GdeYdheGJ hGdeYQaI (B/s ((3GdbGgQI(B: s (3GdefXeI GdYQHjI ddJfejI GdGOGQjI(B, s, 2007)
(3eLJeY GdeYdheGJ hGdeYQaI aj GdYGde GdYQHj, OhQ GdGHOGY hGdGHJcGQ aj HfGA GbJUGO GdeYQaI, GddZI GdYQHjI hGdGSJKeGQ GdeYQaj, BdjGJ MTO GdehGQO GdeGdjI dJehjd CfTWI GdGbJUGO GdeYQaj, (BThe busines plan and knowledge marketing strangy challenges (3NOeI LgjfI, fMh QDjI hGVMI deJWdHGJ GdHjFI GdJMJjI aj GOGQI GdeYQaI defXeGJ GdGYeGd GdYQHjI, JcfhdhLjG GdeYdheGJ hGdCHYGO GdCSGSjI ddJfejI GdHTQjI aj GdhWf GdYQHj, GOGQI eTGQjY GdecJHGJ GdQbejI GdYQHjI aj HjFI GdeYQaI, BdjGJ JWhjQ JTQjYGJ GdedcjI GdacQjI heYGjjQ Jbjje GdeMJhi GdYQHj, Jbjje GUhd GdedcjI GdacQjI heYGjjQ Jbjje GdeMJhi GdYQHj, OhQ GdbVGA hGdJMcje aj aV efGRYGJ Mbhb GdedcjI GdacQjI, OhQ GdbWGY GdNGU GdGSJKeGQj hbWGYGJ GdeLJeY GdeOfj, SjGSGJ GdJfejI GdHTQjI hOhQgG aj JgjFI GdeLJeYGJ GdYQHjIs
(3HHdjhZQGajG(B: (3U(B.328s
Keywords: (3GdGSJKeGQs; (3GdeYQaIs; (3GdeYdheGJs